Risks of Severe Assault and Intimate Partner Homicide among Transgender and Gender Diverse Intimate Partner Violence Survivors: Preliminary Findings from Community Listening Sessions - Sherman, Athena D. F. (Violence against women, 2024)
Intimate partner violence (IPV) is an epidemic among transgender and gender diverse (TGD) people. However, intimate partner homicide (IPH) among TGD people is under researched. Thus, thematic content analysis was used to describe and examine antecedents of severe assault and IPH among TGD adults who have experienced IPV (N = 13), via community listening sessions. While some themes resembled known severe assault and IPH risks among cisgender women, several themes were unique to TGD people and should be considered when safety planning with TGD individuals or adapting IPV screening tools for this population.